The effect of external application of a paste of leaves of Achyranthes aspera L. on bleeding time: A pilot study: Gamage V.G.M.N. and Munasinghe D.A.L (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
Usage of medicinal flora as home remedies is popular in the modern society due to economic benefits. Achyranthes aspera (Apamarga, Karal heba), is a valuable plant and a paste of leaves of it, is applied on minor wounds by Sri Lankans to prevent bleeding. As it is important to investigate the pharmacodynamic properties of the plant on wound bleeding, the current study was caried out to detect the effect of Achyranthes aspera leaves on bleeding time. The setting was the Faculty of Indigenous Medicine. The undergraduates of the faculty were considered as the target group as it was less cumbersome and to reduce age gap issues. Bleeding time was tested with less invasive Duke method. Normal bleeding time of the selected group (n=16) was obtained as the control. The same group was used for the test also and this was to overcome the issues such as age gap, sex gap and health differences. In the test, a paste of pure crushed leaves (25 mg) of the plant was applied to the pricked site. Then, at every 30 seconds, the site was observed for bleeding with the blotting paper (by removing the paste and touch the area with paper). The bleeding time was obtained at the time of stoppage of bleeding. The average bleeding times of control and test was 63.35 and 37.50 seconds respectively and the difference was statically significant (P<0.05) under the paired t test. Thus, this confirms that the bleeding time has been significantly reduced by the materials of crushed plant leaves. Bleeding time is regulated mainly by the formation of platelet plug and constriction of blood vessels in the wound area. Reduction of bleeding time by the plant material, could be due to the phytochemicals such as flavonoids, tannins, which possesses astringent effect with which reduce the blood flow to the wound area. Further, phytochemicals which have anti prostaglandin property also reduce the vasodilation. Thus, the study will be a platform for scientists to conduct more research on the Achyranthes and develop a novel drug for wound bleeding.